2020
DOI: 10.1111/pde.14273
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic sympathicotomy for the treatment of intolerable palmar and axillary hyperhidrosis in children is associated with high recurrence rates

Abstract: Primary hyperhidrosis is a dermatologic condition characterized by excessive sweating beyond that needed for physiologic thermoregulation, without an underlying systemic condition. 1 Primary hyperhidrosis usually affects one or more distinct body sites and, therefore, is also referred to as primary focal hyperhidrosis (PFH). 2 PFH has a wide range of reported estimated prevalence, 3-5 with the most widely cited population prevalence estimate of 2.8%. 4 A recent study estimated population prevalence at 1 to 1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
4
1
2
Order By: Relevance
“…Despite the high recurrence and reoperation rates in our study, overall patient satisfaction was high with a median satisfaction score of 7.5 (interquartile range of 1.75; range 4-9) [6]. Accordingly, Mol et al recently showed high postoperative satisfaction (average score of 9) despite a high rate of compensatory sweating (65%) following thoracoscopic sympathicolysis in children up to and including 14 years of age [10].…”
contrasting
confidence: 51%
See 3 more Smart Citations
“…Despite the high recurrence and reoperation rates in our study, overall patient satisfaction was high with a median satisfaction score of 7.5 (interquartile range of 1.75; range 4-9) [6]. Accordingly, Mol et al recently showed high postoperative satisfaction (average score of 9) despite a high rate of compensatory sweating (65%) following thoracoscopic sympathicolysis in children up to and including 14 years of age [10].…”
contrasting
confidence: 51%
“…Finally, and most importantly, we recently published our results of bilateral, one-stage, single-port sympathicotomy (BOSS) for the treatment of intolerable palmar and axillary PFH (HDSS of 4) in children up to and including 16 years of age and, in this study, we found a high recurrence (50%) and reoperation rate (35.7%) [6]. Reoperations were associated with placement of additional thoracoscopic ports, intraoperative placement of pleural drains, and prolonged air leak [6].…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Only patients rating the severity of their PFH as severe (HDSS 3) or intolerable (HDSS 4) qualify for surgery. Due to a higher recurrence rate of PFH in children younger than 17 years of age, an HDSS score of 4 is mandatory before surgery is even considered in children [41].…”
Section: Selection Of Patients For Minimally Invasive Sympathicotomy For Palmar Hyperhidrosismentioning
confidence: 99%